Sedentary behavior is associated with musculoskeletal pain in adolescents: A cross sectional study - da Costa, Lucas [UNESP]; Lemes, Italo Ribeiro; Tebar, William R. [UNESP]; Oliveira, Crystian B.; Guerra, Paulo H.; Soidán, José Luiz G; Mota, Jorge; Christofaro, Diego G D [UNESP] (Elsevier, 2022)
BACKGROUND: High prevalence of back pain has been observed in adolescents. Sedentary behavior (SB) is considered a risk factor for musculoskeletal pain. The association between back pain and SB in the pediatric/adolescent population is not well established. OBJECTIVE: To investigate the association between SB and low back and neck pain in adolescents according to sex. METHODS: This is a cross-sectional study with children and adolescents aged 10-17 years, randomly recruited from public and private schools in Presidente Prudente, Brazil. All students enrolled in the selected schools were eligible to participate. SB was evaluated by adding the number of hours of use of screen devices, such as television, computer, video game, and smartphone/tablet. To assess neck and low back pain, the Nordic Musculoskeletal Questionnaire was used. Physical activity and socioeconomic status were assessed by the Baecke Questionnaire and the Brazilian Criteria for Economic Classification (ABEP), respectively. Odds ratio (OR) from Binary Logistic Regression in the unadjusted and adjusted model (physical activity, abdominal obesity, and socioeconomic status) showed the relationship between musculoskeletal pain and SB. RESULTS: A total of 1011 adolescents (557 girls) with a mean ± standard deviation age of 13.2±2.4 years were included. Moderate (OR = 1.80; 95%CI: 1.00, 3.23) and high (OR = 1.91; 95%CI: 1.02, 3.53) SB were associated with neck pain in girls. In boys, moderate SB (OR = 2.75; 95%CI: 1.31, 5.78) were associated with neck pain. Moderate (OR = 2.73; 95%CI: 1.45, 5.02) and high (OR = 2.49; 95%CI: 1.30, 4.76) SB were associated with low back pain only in girls. CONCLUSION: Moderate and high SB were associated with neck pain in girls and boys, while moderate and high SB were associated with low back pain only in girls.
Keywords: Low back pain; Motor behavior; Neck pain; Screen time; Spine disorders; Youth